The Contemplative Classroom, or Learning by Heart in the Age of Google. - Newman, Barbara (Buddhist-Christian Studies, 2013)
The article offers the author's insights on the importance of contemplative learning in the rise of social media. The author states that digital culture teaches the people that the most efficient way to work is to multitask which can be a sad necessity of an active life. She mentions that one of the contemplative skills that develops out of silence is active listening. She adds that memory cultivation plays an essential role in contemplative practice.